Neotropical refugia - Bennett, K; Bhagwat, SA; Willis, K (2012)
Patterns of endemism in the Neotropics have been explained by restriction of forest to 'refugia' in arid cold-stages of the Quaternary (Haffer J (1969) Speciation in Amazonian forest birds. Science 165: 131-137). The palaeoecological record, however, shows no such forest contraction. We review palaeoecological and phylogenetic data on the response of Neotropical taxa and communities to climatic changes of the Cenozoic. Solar insolation varies over this period with latitude and geography, including shifts in opposite directions between high and low latitudes. In the Neotropics, distribution and abundance patterns originate on a wide range of timescales through the Cenozoic, down to the currently dominant precession forcing (20 kyr). In contrast, distributions and abundances at higher latitudes are controlled by obliquity forcing (40 kyr). The patterns observed by Haffer (1969) are likely derived from pre-Quaternary radiations and are not inconsistent with palaeoecological findings of continuous forest cover in major areas of the Neotropics during the Quaternary. The relative proportions of speciation processes have changed through time between predominantly sympatric to predominantly allopatric depending on the prevailing characteristics of orbitally forced climatic changes. Behaviour of Neotropical organisms and ecosystems on long timescales may be influenced much more by precessional forcing than by the obliquity forcing that controls high-latitude climate change and glaciations. © The Author(s) 2012.